2002
DOI: 10.1081/ese-120004523
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Adsorption by Crude Coniferous Barks: A Modelling Study

Abstract: Equilibria and mechanisms involved in the adsorption process of metal ions (Cr3+, Cu2+, Ni2+, Pb2+ and Zn2+) from aqueous solutions using coniferous barks as biosorbent substrate were investigated. Crude barks were used in this study since previous experiments showed a decreasing uptake for chemically treated barks in the considered granulometry. In our experimental conditions, the maximum binding capacity of barks followed the decreasing order Cr3+ > Cu2+ > Pb2+ > Ni2+ > Zn2+ whereas their general binding aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…With a q max of 1.16 meq.g -1 (138 mgU.g -1 ) and a b value of 6.1 L.meq -1 , barks proved to easily adsorb uranium. In similar experimental conditions (Martin-Dupont et al, 2002), the uranium adsorption capability of Douglas fir barks appears to be at least five times that of lead, a common heavy metal with a charge similar to UO 2 2+ and a mass of 207 g.mol -1 (270 g.mol -1 for UO 2 2+ ). With q max = 1.4 meq.g -1 (166 mgU.g -1 ) and b = 4.1 L.meq -1 , the data obtained in our laboratory experimental conditions with Amberlite IR120, a common synthetic cation exchange resin, are similar.…”
Section: Adsorption Isotherms and Langmuir Modelingmentioning
confidence: 89%
See 1 more Smart Citation
“…With a q max of 1.16 meq.g -1 (138 mgU.g -1 ) and a b value of 6.1 L.meq -1 , barks proved to easily adsorb uranium. In similar experimental conditions (Martin-Dupont et al, 2002), the uranium adsorption capability of Douglas fir barks appears to be at least five times that of lead, a common heavy metal with a charge similar to UO 2 2+ and a mass of 207 g.mol -1 (270 g.mol -1 for UO 2 2+ ). With q max = 1.4 meq.g -1 (166 mgU.g -1 ) and b = 4.1 L.meq -1 , the data obtained in our laboratory experimental conditions with Amberlite IR120, a common synthetic cation exchange resin, are similar.…”
Section: Adsorption Isotherms and Langmuir Modelingmentioning
confidence: 89%
“…The ability of barks to remove heavy metal ions from polluted solutions (Al-Asheh et al, 1998;Gaballah et al, 1997;Gloaguen et al, 1997;Seki et al, 1997;Aoyama et al, 1993;Deshkar et al, 1990;Kumar et al, 1980;Randall et al, 1974) and the impact of various operating factors on this phenomenon (Deshkar et al, 1990) are well documented. In one of our precedent papers, these interactions were modeled using a Langmuir isotherm (Martin-Dupont et al, 2002) and adsorbent performances were improved using chemical modification by attachment of anionic functions (Martin-Dupont et al, 2004). This article aims to demonstrate the high stability of coniferous barks that should be considered not only as an additional biosorbent but also as an adsorption resin from a biological origin.…”
Section: Introductionmentioning
confidence: 99%
“…With temperature increase, the adsorption of metals increases, although the effect of temperature is small in the 4-25°C range (Martin-Dupont et al 2002). Ghodbane et al (2008) showed that maximum cadmium (II) uptake capacity of Eucalyptus bark increased from 14.53 to 16.47 mg/g when the temperature increased from 20 to 50°C.…”
Section: Heavy Metals Adsorption On Barkmentioning
confidence: 99%
“…Third, the metal speciation in solution is pH dependent, and at higher pH values, metal hydroxide complexes and precipitates can be formed (Naja et al 2009). Metal adsorption onto bark normally occurs under slightly acidic conditions and within the first minutes of contact time (Martin-Dupont et al 2002).…”
Section: Heavy Metals Adsorption On Barkmentioning
confidence: 99%
See 1 more Smart Citation